NLM Medical Library Resource Improvement Grant Program: an evaluation. - Matheson, N W (1976)
The Extramural Programs, NLM, undertook a staff study to evaluate the Medical Library Resource Improvement Grant Program in order to determine impact on hospital library development and to assess factors significant to regional medical library (RML) network development. Initiated in fiscal year 1971, the improvement grant program provides one-year, one-time grant awards of a maximum of $3,000 to assist in establishing a basic collection of books, journals, and other health science information resources for community hospitals and comparable health facilities. Applicants who received grant awards were compared to applicants who did not receive awards and to nonapplicants, using nine dependent variables, four independent variables, and responses to an RML questionnaire. Results show that the applicants who received awards outperformed the other groups, and that the improvement grant program has been successful in stimulating library development. As a result of this study, the improvement grant program will be modified to support consortium arrangements as well as individual institutions, and to extend the period of grant support to two years. Future grant support will be a maximum of $4,000 in the first year, and up to $3,000 with a provision of $1,000 in matching funds from the grantee in the second year.